Reflections on the development and perspectives of anthroponomastic studies in Cuba. (Islas, 2023)
Introduction: Anthroponomastics studies in Cuba have experienced a rise in the last five years. The development level reached allows to comment on the achievements obtained, as well as to identify the main challenges and perspectives.Methods: These reflections are based on an exhaustive bibliographic search of the antecedents on the subject, as well as the exchange with Cuban and foreign specialists in the framework of congresses and conferences.Results: The causes, consequences and possible solutions to the process of invisibilization of Cuban research antecedents are identified and the most updated periodization of these studies is presented. In addition, development actions are proposed in line with national interests and the trends and possibilities in Latin America and the Caribbean.Conclusions: The development of new themes and methodologies, as well as the training of new researchers will contribute to the characterization of the Cuban denominative system within the context of Latin American anthroponomastics integration.
Keywords: Cuba; anthroponomastic studies; research perspectives; periodization